Preparation method of compact block carbon material based on green low-cost biomass water-soluble saccharide small molecular substances
Through the preparation method of dense bulk carbon materials based on green and low-cost biomass water-soluble sugar small molecule substances, the problems of long production cycle, complex process, high energy consumption and dependence on non-renewable resources in the existing graphite material preparation process are solved, and high density and high strength dense carbon materials are prepared, with the advantages of green environmental protection and high efficiency performance.
Patent Information
- Application Number
- CN202510014977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The existing graphite material preparation process has problems such as long production cycle, complex process, high energy consumption and strong dependence on non-renewable fossil resources. The product structure is often heterogeneous and the improvement of mechanical properties is limited.
The dense bulk carbon material preparation method based on green and low-cost biomass water-soluble carbohydrate small molecule substances is adopted. By mixing the water-soluble carbohydrate small molecule with gel monomers, crosslinking agents and initiators, a hydrogel is formed, and after drying, step-up heating and carbonization, crushing, ball milling and other steps, it is finally sintered by hot press sintering, discharge plasma sintering or hot isostatic pressure to prepare a dense carbon material with high density and high strength.
It significantly reduces the dependence on coal-based and petroleum-based raw materials, realizes a green and environmentally friendly production process, improves carbon yield and mechanical properties, and has a wide range of industrial application prospects.
Smart Images

Figure CN119797922A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to a method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances. Background Art
[0002] Carbon (graphite) materials have become indispensable materials in the industrial field due to their unique electrical conductivity, thermal conductivity, mechanical strength and thermal stability. In high temperature and harsh environments, graphite materials show excellent chemical stability and low thermal expansion characteristics, so they are widely used in many fields such as metallurgy, chemical industry, electronics, semiconductor manufacturing, aerospace and nuclear industry.
[0003] At present, the preparation of graphite materials mainly relies on traditional methods and self-sintering methods. The traditional method usually uses fossil resources such as petroleum coke, asphalt coke or anthracite as aggregates, supplemented by coal tar or artificial resin as a binder, and finally obtains graphite materials through isostatic pressing, high-temperature roasting and multiple impregnation. Although this process is mature, it has problems such as long production cycle, complex process and high energy consumption, and the product structure is often heterogeneous, and the isotropic performance is insufficient, which limits the improvement of mechanical properties. In contrast, the self-sintering method uses self-sintering powder (such as raw petroleum coke powder or mesophase asphalt-based powder) and directly treats it at high temperature after compression molding, reducing the use of binders. However, this method has high requirements on powder quality and usually requires modification, which leads to increased production costs. In addition, material shrinkage and cracks are prone to occur during high-temperature treatment, affecting the yield rate. More importantly, these methods are highly dependent on non-renewable fossil raw materials, and the preparation process also involves the use of harmful substances, which brings about problems of environmental pollution and resource consumption, which is inconsistent with the current demand for green and sustainable production.
[0004] Therefore, developing a new method for preparing graphite materials that is efficient, environmentally friendly, and resource-sustainable is an important challenge facing the current technology field. Summary of the invention
[0005] The present invention aims at the problems of long production cycle, complex process, high energy consumption and strong dependence on non-renewable fossil resources in the existing graphite material preparation process, and proposes a preparation method of a dense block carbon material based on green low-cost biomass water-soluble sugar small molecule. The method uses water-soluble sugar small molecules as carbon sources, and then combines gel monomers (such as acrylamide, acrylic acid, methacrylic acid, N-isopropylacrylamide), sintering aids (such as diamond, graphene, graphene oxide, carbon nanotubes and other reinforcing materials; or carbide forming elements such as silicon and titanium; or metal catalysts such as cobalt and nickel; or rare earth elements such as yttrium and lanthanum; or oxides such as aluminum oxide and calcium oxide; or alkali metal compounds such as sodium carbonate and potassium carbonate; or organic additives such as phenolic resin and boric acid esters), which can increase interfacial bonding, participate in reaction, catalyze graphitization during heat treatment, and reduce the difficulty of preparing carbon (graphite) materials.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances comprises the following steps:
[0008] (1) mixing a water-soluble sugar small molecule, a gel monomer, a cross-linking agent and an initiator to obtain a hydrogel, and then sequentially performing drying, step-by-step temperature carbonization, crushing and ball milling to obtain a carbonized powder;
[0009] (2) The carbonized powder and the sintering aid are ball-milled, and then sintered by hot pressing, spark plasma sintering or hot isostatic pressing to obtain the dense bulk carbon material.
[0010] Preferably, the gel monomer includes one or more of acrylamide, acrylic acid, methacrylic acid or N-isopropylacrylamide.
[0011] Preferably, the sintering aid includes one or more of carbon allotropes, carbide-forming element carbides, metal catalysts, metal oxides, rare earth elements, oxides, alkali metal compounds, alkali metal salts or organic aids; wherein the metal catalysts and rare earth elements are in elemental form.
[0012] More preferably, the carbon allotrope includes one or more of diamond, graphene, graphene oxide, carbon nanotubes, and fullerene; and / or
[0013] The carbide-forming elements include one or more of silicon, boron, titanium and zirconium; and / or
[0014] The metal catalyst is one or more of aluminum, iron, cobalt, nickel, calcium, magnesium, and strontium; and / or
[0015] The rare earth element includes one or more of yttrium and lanthanum; and / or
[0016] The oxide comprises one or more of aluminum oxide, calcium oxide and magnesium oxide; and / or
[0017] The alkali metal compound includes one or more of sodium carbonate and potassium carbonate; and / or
[0018] The organic auxiliary agent includes one or more of phenolic resin, furan resin, boric acid ester and organic boron compound.
[0019] Preferably, the water-soluble sugar small molecules include one or more of glucose, fructose, galactose, maltose, sucrose or lactose.
[0020] Preferably, the cross-linking agent includes one or more of N,N'-methylenebisacrylamide, ethylene glycol diacrylate, sodium acrylate, ethylene glycol dimethacrylate, bisacrylamide ethylenediamine, N,N'-ethylenebisacrylamide, etc.;
[0021] The initiator comprises one or more of ammonium persulfate solution, azobisisobutyronitrile, potassium persulfate solution or hydrogen peroxide solution; wherein the solute mass fraction of the ammonium persulfate solution, azobisisobutyronitrile, potassium persulfate solution and hydrogen peroxide solution is 0.5-20%.
[0022] Preferably, the added amount of the sintering aid accounts for 0.1% to 60% of the mass of the carbonized powder.
[0023] Preferably, the temperature during the drying process is 50-200°C, more preferably 80°C.
[0024] Preferably, the conditions during the step-wise temperature carbonization process are:
[0025] First, heat the mixture to 140-350°C at a heating rate of 0.1-20°C / min, and then keep the mixture at this temperature for 2 hours;
[0026] Then, under inert atmosphere conditions, the temperature is first increased to 400-1400° C. at a heating rate of 1-20° C. / min, and then kept at this temperature for 0.5-30 hours.
[0027] Preferably, in step (1), the parameter conditions during the ball milling process are:
[0028] The ball-to-material ratio is 1 to 20:1, the ball mill speed is 100 to 600 r / min, and the ball mill time is 6 to 48 h.
[0029] Preferably, in step (2), the parameter conditions during the ball milling process are:
[0030] Ball milling was performed for 8 hours at a ball-to-material ratio of 3:1 and a rotation speed of 100-200 r / min.
[0031] Preferably, the conditions during the sintering process are:
[0032] The heating rate is 5-300℃ / min, the sintering temperature is 1600-2800℃, the applied pressure is 10-200MPa, and the holding time is 1-120min.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] The present invention successfully prepares high-density, high-strength compact carbon materials through processes such as hot pressing sintering, spark plasma sintering or hot isostatic pressing. Compared with traditional methods, this method significantly reduces the dependence on coal-based and petroleum-based raw materials, realizes a green and environmentally friendly production process, and improves carbon yield and mechanical properties, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0036] Figure 1 The bending strength test results of the graphite block carbon material prepared in Example 1;
[0037] Among them, 1#, 2#, and 3# are three tests of the same sample of graphite bulk carbon material prepared in Example 1;
[0038] Figure 2 The graphite block carbon material compression strength test results prepared in Example 1;
[0039] Figure 3 This is a microstructure diagram of the graphite block carbon material prepared in Example 1. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] The present invention discloses a method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances, comprising the following steps:
[0046] (i) Weigh the gel monomer, water-soluble sugar and cross-linking agent in weight proportions of 1-30%, 5-60% and 0.05-3%, respectively, and add deionized water as the remainder. The amount of deionized water can be adjusted according to specific needs to control the relative proportions of other raw materials in the system.
[0047] (II) The sample preparation process is as follows: First, the gel monomer, water-soluble sugar and cross-linking agent are mixed and dissolved in deionized water, and an initiator aqueous solution with a mass concentration of 0.5-20% is added and stirred to form a uniform solution. The solution is then gelled and dried at 50-200°C to obtain a hydrogel. The hydrogel is then heat-treated in a muffle furnace at 140-350°C, with a heating rate of 0.1-20°C / min, and kept warm for 0.5-30h after reaching the target temperature, and then a pretreated product is obtained. The pretreated product is further carbonized under vacuum / argon / nitrogen conditions, with a heating rate of 1-20°C / min, and kept warm for 0.5-30h after reaching the target temperature of 400-1400°C, to obtain a carbonized product. The carbonized product is crushed and ball-milled in a ball mill, with a ball-to-material ratio of 1-20:1, a ball milling speed of 100-600r / min, and a ball milling time of 6-48h, and carbonized powder is obtained after ball milling.
[0048] Take the carbonized powder, add the sintering aid, and mix them by ball milling. The amount of the sintering aid added accounts for 0.1% to 60% of the mass of the carbonized powder. Then, use hot pressing sintering, spark plasma sintering, or hot isostatic pressing sintering to prepare a high-performance dense bulk carbon material.
[0049] In some preferred embodiments, a mixture of one or more of acrylamide, acrylic acid, methacrylic acid, and N-isopropylacrylamide is selected as the gel monomer;
[0050] Select one or a mixture of multiple sugars such as glucose, fructose, galactose, maltose, sucrose, lactose, etc. as the carbon source.
[0051] In some preferred embodiments, the heating mode is direct heating or step-by-step heating.
[0052] In some preferred embodiments, the sintering aid is one or a mixture of the following:
[0053] (1) Allotropes of carbon: diamond, graphene, graphene oxide, carbon nanotubes, fullerenes;
[0054] (2) Carbide-forming elements: silicon (Si), boron (B), titanium (Ti), zirconium (Zr);
[0055] (3) Metal catalysts: iron (Fe), cobalt (Co), nickel (Ni), calcium (Ca), magnesium (Mg), strontium (Sr);
[0056] (4) Rare earth elements: yttrium (Y), lanthanum (La);
[0057] (5) Oxides: aluminum oxide (Al2O3), calcium oxide (CaO), magnesium oxide (MgO);
[0058] (6) Alkali metal compounds: sodium carbonate (Na2CO3), potassium carbonate (K2CO3);
[0059] (7) Organic additives: phenolic resin, furan resin, boric acid ester, organic boron compound.
[0060] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0061] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0062] The raw materials used in the present invention are all purchased from the market.
[0063] The technical solution of the present invention is further illustrated by the following embodiments.
[0064] Example 1
[0065] First, 24 g of acrylic acid, 80 g of sucrose and 0.6 g of N, N'-methylenebisacrylamide were mixed and dissolved in 220 mL of deionized water, and 6 mL of 10% ammonium persulfate aqueous solution was added and stirred to form a uniform transparent solution. The solution was gelled at 80 ° C and dried for 24 hours to obtain a dried hydrogel. Subsequently, the hydrogel was heated to 240 ° C in a muffle furnace at a heating rate of 0.5 ° C / min, and the pretreated product PG-240 was obtained after 2 hours of heat preservation. The PG-240 sample was heated to 500 ° C at 2 ° C / min in an argon environment and kept warm for 1 hour to obtain a carbonized product PG-500. The PG-500 sample was crushed and ball milled in a ball mill at a ball-to-material ratio of 3: 1 and a speed of 200 r / min for 24 hours to obtain a carbonized powder.
[0066] Take 20g of carbonized powder and add 4g of diamond powder with a particle size of 100nm. Mill it in a ball mill at a ball-to-material ratio of 3:1 and a speed of 100r / min for 6 hours to obtain a uniform mixed powder. Put the mixed powder into a C / C composite material mold with a diameter of 20mm and sinter it using spark plasma sintering technology. The sintering parameters are heating rate 200℃ / min, sintering temperature 2000℃, sintering pressure 100MPa, holding time 10min, and furnace cooling. Through this sintering process, a dense, high-strength bulk carbon material is finally obtained.
[0067] Example 2
[0068] First, 20 g of N-isopropylacrylamide, 60 g of sucrose and 0.6 g of ethylene glycol diacrylate were mixed and dissolved in 200 mL of deionized water, and 6 mL of 10% azobisisobutyronitrile aqueous solution was added and stirred to form a uniform transparent solution. The solution was gelled at 90 ° C and dried for 24 hours to obtain a dried hydrogel. Subsequently, the hydrogel was heated to 200 ° C at a heating rate of 1 ° C / min in a muffle furnace, and the pretreated product PG-200 was obtained after 6 hours of heat preservation. The PG-200 sample was heated to 600 ° C at 5 ° C / min in a vacuum environment and kept warm for 2 hours to obtain a carbonized product PG-600. The PG-600 sample was crushed and ball milled in a ball mill at a ball-to-material ratio of 5: 1 and a speed of 250r / min for 16 hours to obtain a carbonized powder.
[0069] Take 20g of carbonized powder and add 2g of boron powder with a particle size of 80nm. Ball mill it in a ball mill at a ball-to-material ratio of 3:1 and a speed of 150r / min for 8 hours to obtain a uniform mixed powder. Put the mixed powder into a graphite mold with a diameter of 30mm and sinter it using hot pressing sintering technology. The sintering parameters are heating rate 10℃ / min, sintering temperature 1800℃, sintering pressure 60MPa, holding time 120min, and furnace cooling. Through this sintering process, a dense, high-strength bulk carbon material is finally obtained.
[0070] Example 3
[0071] Take 60g of acrylamide, 200g of glucose and 1.5g of N,N'-methylenebisacrylamide, and 500mL of deionized water. Dissolve all the raw materials in deionized water and stir until they are in a uniform and transparent solution state. The solution is gelled at 95°C and dried for 20 hours to obtain a hydrogel. Subsequently, the hydrogel is heated to 220°C in a muffle furnace at a heating rate of 0.5°C / min, and the pretreated product PG-220 is obtained after keeping warm for 2 hours. The PG-220 sample is crushed and ball-milled in a ball mill at a ball-to-material ratio of 10:1 and a speed of 200r / min for 16 hours to obtain a pre-carbonized powder.
[0072] Weigh 60g of pretreated powder (PG-220) and put it into the mold. Use a hydraulic press to perform isostatic pressing, apply a pressure of 200MPa, and maintain the pressure for 10-15 minutes to form a green body. Put the green body into the hot isostatic pressing equipment, heat up to 2200℃ at a rate of 5℃ / min, keep it warm for 2 hours in a nitrogen environment, and maintain the pressure at 100MPa. After the heating is completed, slowly cool down (10℃ / min) and cool to room temperature in a nitrogen environment.
[0073] Comparative Example 1
[0074] This comparative example adopts the preparation process of CN 115849362A to prepare the carbon material, and the specific steps are:
[0075] (1) Step 1: preparing mixed solution, initiating gelation and preliminary dehydration:
[0076] Weigh 1.2 g of analytically pure N,N'-methylenebisacrylamide and put it into a beaker, add 90 g of deionized water, stir thoroughly to dissolve and clarify, slowly add 180 g of analytically pure glucose monohydrate while stirring in a 60°C water bath, dissolve until clarified, naturally cool to 40°C, slowly add 36 g of analytically pure acrylamide, and continue stirring until the solution is clarified to obtain a mixed solution; drop 0.6 g of a 10 wt% ascorbic acid aqueous solution and a 5 wt% hydrogen peroxide aqueous solution into the mixed solution, quickly stir evenly, pour into a mold, stand and wait for gelation, take out after the gel exotherm ends, obtain a hydrogel block, cut into pieces, put into an oven at 100°C for drying and dehydration for 48 hours, and obtain a xerogel;
[0077] (2) Step 2: Gel heat treatment and powder preparation:
[0078] A large amount of dry gel with free water removed is placed in the inner lining of the reactor, and analytical pure acetone is poured in to make the liquid level reach 2 / 3 of the volume. The lid is tightly covered and sealed in the outer lining. The sealed reactor is placed in an oven and the program is set to keep warm at 200°C for 8 hours. After the insulation is completed, it is cooled to room temperature. The block material in the reactor is taken out and the surface liquid is dried; the taken out block material is mechanically crushed to screen out particles below 20 mesh, and the particles are divided into two portions and poured into two planetary ball mills with a volume of 1L respectively, with a material-ball ratio of 1:1, of which the matching Zirconia ball milling beads occupy 1 / 3 of the volume, and the ball milling media are zirconia beads with particle sizes of 5mm, 10mm and 15mm. The mass ratio of 5mm, 10mm and 15mm zirconia beads is 5:3:2; the parameters of the planetary ball mill are set as follows: first run at a speed of 500r / min for 10min, then adjust to 360r / min and continue to run for 6h before shutting down, and the ground powder is passed through a 100-mesh sieve and sealed to prevent moisture. Finally, about 76g of powder raw material can be screened out from each jar.
[0079] (3) Step 3: Warm pressing, carbonization and graphitization:
[0080] 32 g of the prepared raw material powder was weighed and loaded into a Φ50 mm graphite mold for warm pressing. The temperature was slowly increased at a rate of 3°C / min and uniaxial pressurization was performed. The temperature was kept at 180°C, 220°C, 260°C and the highest temperature of 300°C for 30 minutes respectively, then the temperature was reduced to 220°C at a rate of 2°C / min and naturally cooled to room temperature to obtain a prefabricated body. The pressure reached a peak of 8 tons before keeping at 260°C, and slowly dropped to 6 tons before keeping at 300°C. No additional loading was performed during the cooling stage, and the temperature was unloaded when it dropped to below 200°C. After cooling to room temperature, the pressed body was taken out, and the mass of the body was about 27 g.
[0081] The pressed body is placed in an argon atmosphere tubular furnace at 1000°C for 1 hour to obtain a carbonized block, with a heating rate of 3°C / min and a cooling rate of 2°C / min. After cooling to 400°C, it can be cooled naturally. The carbonized block is then graphitized at 3000°C for 10 hours and finally cooled to room temperature to obtain a graphitized block, from a pressed block to a graphitized block.
[0082] The compressive strength of the carbon material prepared in Comparative Example 1 is 112 MPa; and the flexural strength is 57 MPa.
[0083] Figure 1 The graphite block carbon material bending strength test results prepared in Example 1; Figure 1 It can be seen that the carbon material prepared by this method in Example 1 has excellent mechanical properties, and the flexural strength reaches 162MPa.
[0084] Figure 2 The graphite block carbon material compression strength test results prepared in Example 1; Figure 2 It can be seen that the carbon material prepared by this method in Example 1 has excellent mechanical properties and the compressive strength reaches 306 MPa.
[0085] Figure 3 This is the microstructure diagram of the graphite block carbon material prepared in Example 1. It can be seen from the figure that the microstructure of the sample is mainly composed of carbon onions, large flake graphite and amorphous carbon. The carbon onions come from diamonds and can effectively prevent the development of large flake graphite cracks, thereby improving the mechanical properties of the material.
[0086] By comparison, it can be clearly seen that the mechanical strength of the carbon material prepared in Comparative Example 1 is much lower than the compressive strength and flexural strength of the carbon material prepared in Example 1.
[0087] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances, characterized in that: The following steps are involved: (1) mixing a water-soluble sugar small molecule, a gel monomer, a cross-linking agent and an initiator to obtain a hydrogel, and then sequentially performing drying, step-by-step temperature carbonization, crushing and ball milling to obtain a carbonized powder; (2) The carbonized powder and the sintering aid are ball-milled, and then sintered by hot pressing, spark plasma sintering or hot isostatic pressing to obtain the dense bulk carbon material.
2. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1 is characterized in that: The added amount of the sintering aid accounts for 0.1% to 60% of the mass of the carbonized powder.
3. A method for preparing a dense bulk carbon material based on green, low-cost biomass water-soluble sugar small molecule substances according to claim 1 or 2, characterized in that: The sintering aid includes one or more of carbon allotropes, carbide-forming elements, metal catalysts, rare earth elements, oxides, alkali metal compounds or organic aids.
4. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 3 is characterized in that: The carbon allotrope comprises one or more of diamond, graphene, graphene oxide, carbon nanotube or fullerene; and / or The carbide-forming elements include one or more of silicon, boron, titanium and zirconium; and / or The metal catalyst is one or more of aluminum, iron, cobalt, nickel, calcium, magnesium, and strontium; and / or The rare earth element includes one or more of yttrium and lanthanum; and / or The oxide comprises one or more of aluminum oxide, calcium oxide and magnesium oxide; and / or The alkali metal compound includes one or more of sodium carbonate and potassium carbonate; and / or The organic auxiliary agent includes one or more of phenolic resin, furan resin, boric acid ester and organic boron compound.
5. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1 is characterized in that: The cross-linking agent is one or more of N,N'-methylenebisacrylamide, ethylene glycol diacrylate, sodium acrylate, ethylene glycol dimethacrylate, bisacrylamide ethylenediamine, and N,N'-ethylenebisacrylamide; and / or The initiator is any one of azobisisobutyronitrile, ammonium persulfate solution, potassium persulfate solution or hydrogen peroxide solution.
6. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1, characterized in that: The temperature during the drying process is 50-200°C.
7. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1, characterized in that: The conditions in the step-by-step temperature carbonization process are: First, heat the temperature to 140-350°C at a heating rate of 0.1-20°C / min, and then keep it at this temperature for 0.5-30h; Then, under inert atmosphere conditions, the temperature is first increased to 400-1400° C. at a heating rate of 1-20° C. / min, and then maintained at this temperature for 0.5-30 hours.
8. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1, characterized in that: In step (1), the parameter conditions during the ball milling process are: The ball-to-material ratio is 1 to 20:1, the ball mill speed is 100 to 600 r / min, and the ball mill time is 6 to 48 h.
9. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1, characterized in that: In step (2), the parameter conditions during the ball milling process are: Ball milling was performed at a ball-to-material ratio of 3:1 and a rotation speed of 100-200 r / min for 6-8 hours.
10. The method for preparing a dense bulk carbon material based on green and low-cost biomass water-soluble sugar small molecule substances according to claim 1, characterized in that: The conditions during the sintering process are: The heating rate is 5-300℃ / min, the sintering temperature is 1600-2800℃, the applied pressure is 10-200MPa, and the holding time is 1-120min.
Citation Information
Patent Citations
Preparation method of block carbon / graphite material based on saccharide small molecules
CN115849362A
Silicon carbide graphite composite material and preparation method thereof
CN103833363A
Method for fixing carbon in saccharides and preparing high-purity carbon (graphite) material
CN104176725A
Preparation method of isotropous graphite block
CN107010957A
Preparation method of compact block ceramic material
CN107954715A